Trace and Macro Element Contaminations in Tissues of Vimba persa and Alosa braschnikowi From the South Caspian Sea and Potential Human Health Risk Assessment - Masoud Sattari; Mehdi Bibak; Mohammad Forouhar Vajargah (Hamadan University of Medical Sciences, 2021)
Alosa braschnikowi and Vimba persa are commercially important fish species in the southern part of the Caspian Sea. However, little is known about the trace element (TE) concentrations in their muscles. To this end, a total of 82 pieces of V. persa and 74 A. braschnikowi were caught at three different fishing areas (Astara, Anzali, and Kiashahr) around the southwestern shorelines of the Caspian Sea from September 2017 through June 2018. An inductively coupled plasma optical emission spectrometry (ICP-OES) was used to measure the accumulation of 34 traces and macro elements in some tissues of the fish species. Then, comparisons of the element levels in these tissues were made for the three different fishing areas. Overall, in the case of A. braschnikowi, 30, 30, and 28 elements were detected in its skin, gonads, and kidneys, respectively, while in the case of V. persa, 27 and 28 elements were found in its muscle and liver, respectively. The majority of element levels measured in these tissues indicated no significant differences among the sampling areas (P>0.05) except for such elements as copper, lanthanum, and tungsten in skin, lanthanum, rubidium, and vanadium in gonads, as well as molybdenum and zinc in kidney (P<0.05). The capacity of observed elements put human health at risk were examined as well. The TE content in the tissues of A. braschnikowi and in the muscles of V. persa (P<0.05) differed significantly from the international standard levels (P<0.05). In this study, only lead indicated a target hazard quotient (THQ) index above 1. Therefore, high consumption of this fish (360 g per year) may be a matter of concern for the consumer. In the case of other evaluated elements, the THQ value was less than 1.